X-ray micro-tomographic data of live larvae of the beetle Cacosceles newmannii - Lehmann, Philipp; Javal, Marion; Plessis, Anton, Du; Tshibalanganda, Muofhe; Terblanche, John (My University, 2021)
Quantifying insect respiratory structures and their variation has remained challenging due to their microscopic size. Here we measure insect tracheal volume using X-ray micro-tomography (µCT) scanning (at 15 µm resolution) on living, sedated larvae of the cerambycid beetle Cacosceles newmannii across a range of body sizes. In this paper we provide the full volumetric data and 3D models for 12 scans, providing novel data on repeatability of imaging analyses and structural tracheal trait differences provided by different image segmentation methods. The volume data is provided here with segmented tracheal regions as 3D models.
Keywords: Development; Imaging; microtomography; Morphology; X-ray tomography